Seismic Retrofit of Concrete Columns by Transverse Prestressing - Sabri, Amirreza (Université d'Ottawa / University of Ottawa, 2013)
Performance of buildings and bridges during past earthquakes has indicated that many of these structures are vulnerable to seismic damage and structural collapse. The deficiencies in pre-1970s design codes have resulted in poor performance of reinforced concrete structures during seismic excitations. The Richter Magnitude 6.6 - 1971 San Fernando Earthquake raised awareness for seismic retrofit needs of existing buildings for the first time. The majority of deficiencies of vulnerable concrete columns can be overcome through seismic retrofits that involve additional transverse reinforcement. This can be done either by providing reinforced concrete, steel, or fibre-reinforced polymer (FRP) jackets around existing columns; or by applying transverse prestressing to columns (RetroBelt System). The research project presented in this thesis involves a seismic retrofit methodology for seismically deficient building and bridge columns, utilizing the use of high-strength packaging straps as external reinforcement for transverse prestressing. The emphasis in the project is placed on experimental research. Three seismically deficient full-size reinforced concrete columns, with a circular, a square and a rectangular cross- section, either critical in shear or flexure, were designed, built and tested under simulated seismic loading. The results indicate that external prestressing of columns in transverse direction with high-strength steel straps improves ductility and energy dissipation capacity of seismically deficient columns. They further indicate that current analytical techniques can be used to predict the force-displacement relationships of columns. A design approach is presented for the retrofit methodology investigated.
Keywords: Seismic; Retrofit; Concrete; Column; Transverse; Prestressing; building; bridge; earthquake; reinforced concrete; seismic retrofit; high-strength packaging straps; transverse reinforcement; RetroBelt; transverse prestressing; simulated seismic loading